2020
DOI: 10.1186/s40478-020-00983-w
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytic α-synuclein contained in microvesicles regulates astrocytic glutamate homeostasis: a new perspective on Parkinson’s disease pathogenesis

Abstract: Parkinson's disease is a neurodegenerative disorder characterized by the transmission and accumulation of toxic species of α-synuclein (α-syn). Extracellular vesicles (EVs) are believed to play a vital role in the spread of toxic α-syn species. Recently, peripheral α-syn pathology has been investigated, but little attention has been devoted to erythrocytes, which contain abundant α-syn. In this study, we first demonstrated that erythrocyte-derived EVs isolated from Parkinson's disease patients carried elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 104 publications
(170 reference statements)
0
36
0
Order By: Relevance
“…Together, these cells form the neurovascular unit and their intercellular exchange is mandatory for BBB integrity and function (112). Studies directly addressing the mechanism of EV-crossing over the endothelial cell layer of the BBB suggested that the EV-transport mechanism is energydependent and can follow dynamin-, clathrin-, and caveolin-mediated as well as macropinocytic transcellular routes rather than paracellular diffusion (126)(127)(128)(129). Additionally, it was shown that uptake of blood-derived EVs by BMECS is, at least in part, mediated by transferrin receptormediated endocytosis (128).…”
Section: Accepted Articlementioning
confidence: 99%
“…Together, these cells form the neurovascular unit and their intercellular exchange is mandatory for BBB integrity and function (112). Studies directly addressing the mechanism of EV-crossing over the endothelial cell layer of the BBB suggested that the EV-transport mechanism is energydependent and can follow dynamin-, clathrin-, and caveolin-mediated as well as macropinocytic transcellular routes rather than paracellular diffusion (126)(127)(128)(129). Additionally, it was shown that uptake of blood-derived EVs by BMECS is, at least in part, mediated by transferrin receptormediated endocytosis (128).…”
Section: Accepted Articlementioning
confidence: 99%
“…alpha-Synuclein has been reported to trigger the opening of connexin 43 (Cx43) hemichannels and pannexin-1 (Panx1) channels in mouse cortical astrocytes, leading to alterations in [Ca 2+ ] i levels, production of nitric oxide (NO), enhanced purinergic and glutamatergic signaling, altered mitochondrial morphology and reduced astrocyte survival [ 599 ]. Another recently published study suggests that vesicle-associated aSyn, deriving from erythrocytes, effectively crosses the BBB and accumulates within astrocytes, impairing glutamate uptake, probably due to interactions of oligomeric aSyn with excitatory amino acid transporter 2 (EAAT2) [ 600 ]. Furthermore, astrocytes overexpressing mutant A35T and A30P aSyn triggered ER stress and damaged the Golgi apparatus, finally leading to apoptotic cell death [ 601 ].…”
Section: Glia In the Cns: Scavengers Of Extracellular Asynmentioning
confidence: 99%
“…In fact, the α-synuclein-induced opening of hemichannels and pannexons resulted in alterations in Ca 2+ dynamics, NO production, gliotransmitter release, mitochondrial morphology, and astrocyte survival. Recently, Sheng et al [142] provided a new perspective on the pathogenesis of PD; erythrocyte-derived α-synuclein in extracellular vesicles was found to readily cross the BBB and accumulate in astrocyte end-feet, where they impaired glutamate uptake, likely via interaction between EAAT2 and oligomeric α-synuclein.…”
Section: α-Synuclein Toxicitymentioning
confidence: 99%